Is Cholesterol and Amyloid-[beta] Stress Induced CD147 Expression a Protective Response? Evidence that Extracellular Cyclophilin A Mediated Neuroprotection is Reliant on CD147 - Kanyenda, L.; Verdile, Giuseppe; Martins, R.; Meloni, B.; Chieng, J.; Mastaglia, F.; Laws, S.; Anderton, R.; Boulos, S. (IOS Press, 2014)
The CD147 protein is a ubiquitous multifunctional membrane receptor. Expression of CD147, which is regulated by sterol carrier protein, reportedly modulates amyloid- (A), the neurotoxic peptide implicated in neuronal degeneration in Alzheimer’s disease (AD). Given that high fat/cholesterol is linked to amyloid deposition in AD, we investigated if cholesterol and/or A can alter CD147 expression in rat cortical neuronal cultures. Water-soluble cholesterol and A42 dose-dependentlyincreased CD147 protein expression, but reduced FL-APP protein expression. Cholesterol and A42 treatment also increased lactate dehydrogenase release but to varying degrees. Upregulation of CD147 expression was probably mediated by oxidative stress, as H2O2 (3M) also induced CD147 protein expression in neuronal cultures. In light of these findings, we investigated if CD147 induction was cytoprotective, a compensatory response to injury, or alternatively, a cell death signal. To this end, weused recombinant adenovirus to overexpress human CD147 (in SH-SY5Y cells and primary cortical neurons), and pre-treated cultures with or without recombinant cyclophilin A (rCYPA) protein, prior to A42 exposure.We showed that increased CD147 expression protected against A42, only when rCYPA protein was added to neuronal cultures. Together, our findings reveal potentially important relationships between cholesterol loading, CD147 expression, A toxicity, and the putative involvement of CYPA protein in neuroprotection in AD.